Outcomes after stroke thrombolysis according to prior antiplatelet use. Issue 2 (8th December 2014) - Meseguer, Elena; Labreuche, Julien; Guidoux, Celine; Lavallée, Philippa C.; Cabrejo, Lucie; Sirimarco, Gaia; Valcarcel, Jaime G.; Klein, Isabelle F.; Amarenco, Pierre; Mazighi, Mikael
<x xml:space="preserve">Abstract</x> Background Thirty percent of ischemic stroke (IS) patients suffering from acute stroke are under antiplatelet therapy. Aims We evaluated whether prior antiplatelet use before intravenous (IV), intra‐arterial (IA) or combined IV/IA therapy may be associated with worse outcomes and an increased intracerebral hemorrhage (ICH) risk after reperfusion therapies. Methods We analyzed data from our patient registry (n = 874) and conducted a systematic review of previous observational studies. The primary outcome was the percentage of patients who developed symptomatic ICH (sICH), defined in our registry per ECASS‐II definition. Results We identified 43 previous reports that evaluated the impact of prior antiplatelet use on outcomes after reperfusion therapy in AIS patients. Prior antiplatelet use was found in 35% of AIS patients, eligible for reperfusion therapies and was associated with a worse vascular profile. In an unadjusted meta‐analysis that included our registry data, prior antiplatelet use was associated with more sICH per ECASS‐II definition (OR, 1·78 (95% CI, 1·48–2·13), and less favorable outcome (OR, 0·86; 95% CI, 0·77–0·98). However, in multivariate analyses conducted in our registry showed that prior antiplatelet use was not associated with worse outcome (P > 0·23); and in the systematic review, only 3 studies reported a slight, but significant adjusted increase in sICH risk, of whom one had conflicting results according to sICH definition. Conclusions These results suggest no significant detrimental effect of prior antiplatelet use in AIS patients treated by IV, IA or combined IV/IA therapy. Further studies are needed to assess the specific impact of different and cumulative antiplatelet agents.